Sodium-ion battery positive electrode material as well as preparation method and application thereof

By doping boric acid during the sintering process of the positive electrode material of sodium ion battery, the problems of high sintering temperature and high residual alkali content are solved, and the energy density, circulation and safety performance of the material are improved, simplified the production process and reduced costs.

CN119864419APending Publication Date: 2025-04-22HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311360428.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-19
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

During the sintering process, the positive electrode material of sodium ion battery has a high sintering temperature and high residual alkali content, resulting in high production costs, high technical difficulty, reduced energy density and cycling performance, and poor safety performance.

Method used

Doping boric acid during the sintering process reduces the sintering temperature and residual alkali content through fusion effect, and improving the energy density, circulation and safety performance of the material.

Benefits of technology

It is achieved by reducing the sintering temperature and residual alkali content without affecting the material structure, improving the energy density, circulation performance and safety performance of the positive electrode material of sodium ion battery, simplifying the production process and reducing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864419A_ABST
    Figure CN119864419A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery positive electrode material and a preparation method and application thereof. The preparation method of the sodium ion battery positive electrode material provided by the invention comprises the following steps: mixing a sodium ion battery positive electrode precursor or a transition metal oxide with H3BO4 and a sodium source to obtain a mixture; and sintering, cooling, crushing and sieving the mixture to obtain the sodium ion battery positive electrode material. The boric acid is doped in the sintering process of the sodium-ion battery positive electrode material, so that the aim of simultaneously reducing the sintering temperature and the residual alkali content of the sodium-ion battery positive electrode material in one step can be fulfilled on the premise of not influencing the structure of the sodium-ion battery positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a sodium ion battery positive electrode material and a preparation method and application thereof, belonging to the technical field of sodium ion battery materials. Background Art

[0002] Over the past 20 years, lithium-ion batteries have been successfully used as power sources for portable electronic devices and are now also becoming a promising source of energy for vehicles. However, the production cost of lithium and its uneven geographical distribution may limit its further application in large-scale energy storage. Therefore, the development of cheap, long-cycle life, and high-energy conversion efficiency large-scale energy storage is an urgent need for the integration of renewable energy into the power grid.

[0003] In recent years, sodium-ion batteries have attracted worldwide attention due to their unlimited resources and low cost. In the near future, sodium-ion batteries will become a viable alternative to lithium-ion batteries.

[0004] The sintering temperature of layered structural materials for the positive electrode of sodium-ion batteries is generally higher than that of positive electrode materials for lithium-ion batteries, especially single crystal positive electrodes for sodium-ion batteries. The higher sintering temperature leads to increased production costs and technical difficulties, which hinders the large-scale production and application of sodium-ion batteries. At the same time, due to the defects in the manufacturing process of layered oxide positive electrode materials for sodium-ion batteries and the problems with the material structure, sodium residue will absorb CO2 and H2O in the air to generate Na2CO3 and NaOH residual alkali. This situation is concentrated in the fact that the total amount of residual alkali in a single high-temperature sintering product can be as low as about 20,000 and as high as more than 30,000. Excessive residual alkali will not only make the slurry jelly-like, making the coating process difficult to carry out, but also reduce the energy density and cycle performance of the material. At the same time, it will also cause the gas production problem of the soft pack, resulting in a decrease in battery safety performance.

[0005] Although there are patent documents on doping SrO and other metal oxide fluxes to reduce the sintering temperature, they generally have problems such as high residual alkali content, poor electrical performance and low safety. At the same time, for the problem of high residual alkali content in the positive electrode material of sodium ion batteries, water washing or acid washing is currently used to wash away the residual alkali on the surface of the material. However, during the water washing or acid washing process, a large amount of sodium ions will also be lost along with the removal of residual alkali; at the same time, the erosion of the particle surface by water or acid will lead to a decrease in structural stability. These situations increase the irreversible capacity of the material, resulting in a significant decrease in the energy density and cycle performance of the material. Summary of the invention

[0006] The purpose of the present invention is to provide a sodium ion battery positive electrode material, which can reduce the sintering temperature and residual alkali content of the sodium ion battery positive electrode material in one step without affecting the structure of the sodium ion battery positive electrode material by doping boric acid during the sintering process, and improve the energy density, cycle performance and safety performance of the sodium ion battery positive electrode material. The method is simple and easy to implement and easy to industrialize.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a positive electrode material for a sodium ion battery, comprising the following steps:

[0009] S1, mixing a sodium ion battery cathode precursor or a transition metal oxide with H3BO4 and a sodium source to obtain a mixture;

[0010] S2, sintering the mixture, cooling it, crushing it and screening it to obtain the positive electrode material for the sodium ion battery.

[0011] In step S1, the positive electrode precursor of the sodium ion battery is Ni a Fe b Mn c M d (OH)2, wherein a+b+c+d=1, and M is selected from any one or more of Cu, Mg, Zn, Co, Al, Zr, Ca, W and Ti. Specifically, the positive electrode precursor of the sodium ion battery can be Ni a Fe b Mn c (OH)2.

[0012] In step S1, the transition metal oxide comprises at least a nickel source, an iron source and a manganese source. The nickel source is nickel oxide. The iron source is iron oxide and / or ferroferric oxide. The manganese source is manganese oxide and / or manganese tetraoxide.

[0013] In step S1, the transition metal oxide may further include an oxide containing M, where M is selected from any one or more of Cu, Mg, Zn, Co, Al, Zr, Ca, W and Ti.

[0014] In step S1, the molar ratio of the H3BO4 to the total metal elements in the sodium ion battery positive electrode precursor is (0.0005-0.01):1, preferably (0.001-0.006):1.

[0015] The molar ratio of the H3BO4 to the total metal elements in the transition metal oxide is (0.0005-0.01):1, preferably (0.001-0.006):1.

[0016] In step S1, the sodium source is one or more of sodium carbonate, sodium acetate, sodium oxalate, sodium chloride, sodium nitrate and sodium citrate.

[0017] In step S1, the molar ratio of the sodium element in the sodium source to the total metal elements in the sodium ion battery positive electrode precursor is 1:(0.5-2), preferably 1:1.05.

[0018] In step S1, metal salts may be doped during the mixing process; the metal salts are one or more of copper oxide, aluminum oxide, calcium oxide, cobalt oxide, zinc oxide, zirconium oxide, lithium oxide, tungsten oxide, titanium oxide and magnesium oxide.

[0019] In step S2, the sintering conditions are: temperature of 700°C-1000°C, preferably 800°C-950°C, specifically 900°C, and time of 15-20h, preferably 15h.

[0020] In step S2, the cooling is to room temperature.

[0021] In step S2, the mesh size of the sieve is 100-200 meshes.

[0022] In a second aspect, the present invention further provides a sodium ion battery positive electrode material obtained by the method.

[0023] The residual alkali content in the sodium ion battery positive electrode material is 100-2000ppm, preferably 100-900ppm.

[0024] The average particle size of the sodium ion battery positive electrode material is in the range of 3-15 μm, preferably 3-10 μm.

[0025] In a third aspect, the present invention further provides a sodium ion battery, comprising a positive electrode and a negative electrode; the positive electrode is the above-mentioned positive electrode material.

[0026] The beneficial effects achieved by the present invention are as follows:

[0027] 1. The present invention can achieve the purpose of reducing the sintering temperature and residual alkali content of the positive electrode material of the sodium ion battery in one step without affecting the structure of the positive electrode material of the sodium ion battery by doping H3BO4 during the sintering process. Boric acid plays a fluxing role in the sintering process of the positive electrode material of the sodium ion battery, which can greatly reduce the sintering temperature, reduce production costs and technical difficulties, and can also reduce the residual alkali content of the positive electrode material of the sodium ion battery, and control the total amount of residual alkali of the sintered product of a high-temperature sintering to less than 2000ppm, avoiding the problems of high residual alkali content of the material leading to a decrease in battery energy density and cycle performance, and reduced safety.

[0028] 2. The H3BO4 doping method proposed in the present invention is not only effective, but also simple and easy to implement and industrialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the sodium ion battery positive electrode material provided in Example 1.

[0030] Figure 2 This is the SEM image of the sodium ion battery positive electrode material provided in Comparative Example 1.

[0031] Figure 3 This is the SEM image of the sodium ion battery positive electrode material provided for Comparative Example 2. DETAILED DESCRIPTION

[0032] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.

[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0034] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.

[0035] Example 1

[0036] Here are the steps:

[0037] (1) Ni, the cathode precursor of sodium ion battery 0.33 Fe 0.33 Mn 0.33 (OH)2, H3BO4 and sodium carbonate are mixed evenly to obtain a mixed material; the molar ratio of the sodium element in the sodium carbonate to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 1:1.05, and the molar ratio of H3BO4 to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 0.005:1.

[0038] (2) The mixed material is heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then the mixed material is cooled to 300°C at a cooling rate of 2°C / min and kept at this temperature for 5 hours; finally, the mixed material is cooled with the furnace to obtain a sintered material; the sintered material is crushed and ground in turn, and the crushed and ground material is passed through a 200-mesh sieve to obtain NaNi with low sintering temperature and low residual alkali content. 0.33 Fe 0.33 Mn 0.33 B 0.005 O2 sodium-ion battery positive electrode layered oxide products.

[0039] The low sintering temperature and low residual alkali content NaNi prepared in this embodiment 0.33 Fe 0.33 Mn 0.33 B 0.005The residual alkali content, average particle size, first charge and discharge and cycle performance of the positive electrode layered oxide product of O2 sodium ion battery are shown in Table 1, and the particle SEM image is shown in Figure 1 .

[0040] The layered oxide material prepared above is used as the active material of the battery positive electrode material for the preparation of sodium ion batteries. The specific steps are: 0.33 Fe 0.33 Mn 0.33 B 0.005 O2 powder is mixed with acetylene black and binder polyvinylidene fluoride (PVDF) in a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) solution is added. The mixture is ground in a dry environment at room temperature to form a slurry, and then the slurry is evenly coated on the current collector aluminum foil and cut into pole pieces after drying under an infrared lamp. The pole pieces are dried at 100°C for 8 hours under vacuum conditions and then transferred to a glove box for standby use. The assembly of the simulated battery is carried out in a glove box with an Ar atmosphere. Metal sodium is selected as the counter electrode, and NaClO4 / propylene carbonate (PC) solution is used as the electrolyte to assemble into button cells.

[0041] The charge and discharge test was carried out using the constant current charge and discharge mode at a current density of 0.2C. The test voltage range was 2.0V to 4.0V. The results are shown in Table 1.

[0042] Example 2

[0043] Here are the steps:

[0044] (1) Ni, the cathode precursor of sodium ion battery 0.33 Fe 0.33 Mn 0.33 (OH)2, H3BO4 and sodium carbonate are mixed evenly to obtain a mixed material; the molar ratio of the sodium element in the sodium carbonate to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 1:1.05, and the molar ratio of H3BO4 to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 0.0005:1.

[0045] (2) The mixed material is heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then the mixed material is cooled to 300°C at a cooling rate of 2°C / min and kept at this temperature for 5 hours; finally, the mixed material is cooled with the furnace to obtain a sintered material; the sintered material is crushed and ground in turn, and the crushed and ground material is passed through a 200-mesh sieve to obtain NaNi with low sintering temperature and low residual alkali content. 0.33 Fe 0.33 Mn 0.33 B 0.0005 O2 sodium-ion battery positive electrode layered oxide products.

[0046] The layered oxide material prepared as above was used as the active material of the positive electrode material of the battery for the preparation of a sodium ion battery, and an electrochemical charge and discharge test was performed. The preparation process and test method were the same as in Example 1. The test voltage range was 2.0V to 4.0V, and the results are shown in Table 1 below.

[0047] Example 3

[0048] Here are the steps:

[0049] (1) Ni, the cathode precursor of sodium ion battery 0.33 Fe 0.33 Mn 0.33 (OH)2, H3BO4 and sodium carbonate are mixed evenly to obtain a mixed material; the molar ratio of the sodium element in the sodium carbonate to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 1:1.05, and the molar ratio of H3BO4 to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 0.01:1.

[0050] (2) The mixed material is heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then the mixed material is cooled to 300°C at a cooling rate of 2°C / min and kept at this temperature for 5 hours; finally, the mixed material is cooled with the furnace to obtain a sintered material; the sintered material is crushed and ground in turn, and the crushed and ground material is passed through a 200-mesh sieve to obtain NaNi with low sintering temperature and low residual alkali content. 0.33 Fe 0.33 Mn 0.33 B 0.01 O2 sodium-ion battery positive electrode layered oxide products.

[0051] The layered oxide material prepared as above was used as the active material of the positive electrode material of the battery for the preparation of a sodium ion battery, and an electrochemical charge and discharge test was performed. The preparation process and test method were the same as in Example 1. The test voltage range was 2.0V to 4.0V, and the results are shown in Table 1 below.

[0052] Comparative Example 1

[0053] Here are the steps:

[0054] (1) Ni, the cathode precursor of sodium ion battery 0.33 Fe 0.33 Mn 0.33 (OH)2 and sodium carbonate are mixed evenly to obtain a mixed material; the molar ratio of the sodium element in the sodium carbonate to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 1:1.05.

[0055] (2) The mixed material was heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then the mixed material was cooled to 300°C at a cooling rate of 2°C / min and kept at this temperature for 5 hours; finally, the mixed material was cooled in the furnace to obtain a sintered material; the sintered material was crushed and ground in turn, and the crushed and ground material was passed through a 200-mesh sieve to obtain NaNi 0.33 Fe 0.33 Mn 0.33 O2 sodium-ion battery positive electrode layered oxide products.

[0056] The NaNi prepared in this example 0.33 Fe 0.33 Mn 0.33 The residual alkali content, average particle size, first charge and discharge and cycle performance of the positive electrode layered oxide product of O2 sodium ion battery are shown in Table 1, and the particle SEM image is shown in Figure 1 .

[0057] The layered oxide material prepared as above was used as the active material of the positive electrode material of the battery for the preparation of a sodium ion battery, and an electrochemical charge and discharge test was performed. The preparation process and test method were the same as in Example 1. The test voltage range was 2.0V to 4.0V, and the results are shown in Table 1 below.

[0058] Comparative Example 2

[0059] Here are the steps:

[0060] (1) Ni, the cathode precursor of sodium ion battery 0.33 Fe 0.33 Mn 0.33 (OH)2 and sodium carbonate are mixed evenly to obtain a mixed material; the molar ratio of the sodium element in the sodium carbonate to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 1:1.05.

[0061] (2) The mixed material is heated to 1000°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then the temperature is cooled to 300°C at a cooling rate of 2°C / min and kept at this temperature for 5 hours; finally, the mixed material is cooled in the furnace to obtain a sintered material; the sintered material is crushed and ground in turn, and the crushed and ground material is passed through a 200-mesh sieve to obtain NaNi 0.33 Fe 0.33 Mn 0.33 O2 sodium-ion battery positive electrode layered oxide products.

[0062] The NaNi prepared in this example 0.33 Fe 0.33 Mn 0.33 The residual alkali content, average particle size, first charge and discharge and cycle performance of the positive electrode layered oxide product of O2 sodium ion battery are shown in Table 1, and the particle SEM image is shown in Figure 1 .

[0063] The layered oxide material prepared as above was used as the active material of the positive electrode material of the battery for the preparation of a sodium ion battery, and an electrochemical charge and discharge test was performed. The preparation process and test method were the same as in Example 1. The test voltage range was 2.0V to 4.0V, and the results are shown in Table 1 below.

[0064] Comparative Example 3

[0065] Here are the steps:

[0066] (1) Ni, the cathode precursor of sodium ion battery 0.33 Fe 0.33 Mn 0.33 (OH)2 and sodium carbonate are mixed evenly to obtain a mixed material; the molar ratio of the sodium element in the sodium carbonate to the nickel, cobalt and manganese elements in the precursor of the positive electrode material of the sodium ion battery is 1:1.05.

[0067] (2) The mixed material was heated to 900°C at a heating rate of 5°C / min and kept at this temperature for 15 hours; then the mixed material was cooled to 300°C at a cooling rate of 2°C / min and kept at this temperature for 5 hours; finally, the mixed material was cooled in the furnace to obtain a sintered material; the sintered material was crushed and ground in turn, and the crushed and ground material was passed through a 200-mesh sieve to obtain NaNi 0.33 Fe 0.33 Mn 0.33 O2 sodium-ion battery positive electrode layered oxide products.

[0068] (3) The obtained NaNi 0.33 Fe 0.33 Mn 0.33 The O2 sodium ion battery positive electrode layered oxide product was mixed with H3BO4 at a mass ratio of 1:0.01, and placed in a ball mill for low-speed ball milling for 2 hours, wherein the ball-to-material ratio was 2:1, to obtain a crude product;

[0069] (4) The obtained crude product is sintered at 500° C. for 5 h in an air atmosphere, and after cooling, a modified sodium ion battery layered ternary positive electrode material is obtained.

[0070] Effect verification

[0071] 1. Structural characteristics

[0072] Depend on Figure 1 , Figure 2 , Figure 3 It can be seen that the sintering temperatures of Example 1 and Comparative Example 1 are both 900° C., the particle size of the positive electrode particles in Example 1 is significantly larger than that in Comparative Example 1, and the particle size of the positive electrode particles in Comparative Example 2 is the same as that in Example 1, but the sintering temperature of Comparative Example 2 is 1000° C. This shows that boric acid doping in Example 1 can significantly reduce the sintering temperature of the positive electrode material of the sodium ion battery.

[0073] 2. Performance Testing

[0074] Table 1 Sintering temperature and performance test of layered ternary cathode materials for sodium ion batteries

[0075]

[0076] It can be seen from the test results in Table 1 that the first week charging specific capacity, first efficiency and cycle efficiency of boric acid doping in Examples 1-3 are higher than those of Comparative Examples 1-3, among which Example 1 is the highest. This shows that by doping H3BO4 during the precursor sintering process, the sintering temperature and residual alkali content of the positive electrode material of the sodium ion battery can be reduced in one step, and the energy density, cycle performance and safety performance of the positive electrode material can be improved.

[0077] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a positive electrode material for a sodium ion battery, comprising the following steps: S1, mixing a sodium ion battery cathode precursor or a transition metal oxide with H3BO4 and a sodium source to obtain a mixture; S2, sintering the mixture, cooling it, crushing it and screening it to obtain the positive electrode material for the sodium ion battery.

2. The preparation method according to claim 1, characterized in that: In step S1, the positive electrode precursor of the sodium ion battery is Ni a Fe b Mn c M d (OH)2; in: a+b+c+d=1; M is selected from any one or more of Cu, Mg, Zn, Co, Al, Zr, Ca, W and Ti; The molar ratio of the H3BO4 to the total metal elements in the sodium ion battery positive electrode precursor is (0.0005-0.01):

1.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the transition metal oxide comprises at least a nickel source, an iron source and a manganese source; The nickel source is nickel oxide; The iron source is iron oxide and / or ferrosoferric oxide; The manganese source is manganese oxide and / or trimanganese tetraoxide.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S1, the transition metal oxide further comprises an oxide containing M, where M is selected from any one or more of Cu, Mg, Zn, Co, Al, Zr, Ca, W and Ti; The molar ratio of the H3BO4 to the total metal elements in the transition metal oxide is (0.0005-0.01):

1.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S1, the sodium source is one or more of sodium carbonate, sodium acetate, sodium oxalate, sodium chloride, sodium nitrate and sodium citrate; The molar ratio of the sodium element in the sodium source to the total metal elements in the sodium ion battery positive electrode precursor is 1:(0.5-2).

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S1, a metal salt is also doped during the mixing process; The metal salt is one or more of copper oxide, aluminum oxide, calcium oxide, cobalt oxide, zinc oxide, zirconium oxide, lithium oxide, tungsten oxide, titanium oxide and magnesium oxide.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step S2, the sintering conditions are: temperature of 700°C-1000°C, and time of 15-20h.

8. A sodium ion battery positive electrode material obtained by the preparation method according to any one of claims 1 to 7.

9. The sodium ion battery positive electrode material according to claim 8, characterized in that: The residual alkali content in the sodium ion battery positive electrode material is 100-2000ppm; The average particle size of the sodium ion battery positive electrode material is in the range of 3-15 μm.

10. A sodium ion battery comprising a positive electrode and a negative electrode; the positive electrode is the sodium ion battery positive electrode material according to claim 8 or 9.

Citation Information

Patent Citations

  • Modified sodium ion battery layered ternary positive electrode material and preparation method thereof

    CN114695853A

  • Sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN116143195A

  • Positive electrode material compositely coated with borate and metal boride and preparation method of positive electrode material

    CN116169271A

  • Monocrystal type sodium ion battery positive active material and preparation method and application thereof

    CN116741950A

  • Method of Preparing Positive Electrode Active Material

    US20230268489A1